FRI0305 Physicians' Perspective on the Reasons for Non-Treatment of Osteoporosis Among Postmenopausal Patients in France – An Observational Study. (9th June 2015) - Olsson, K.; Sadasivan, R.; Weaver, J.; Sen, S.; Modi, A.
Abstract : Background: Osteoporosis (OP) is a common chronic condition in postmenopausal women. Recent studies indicate that 10% 1 to 46% 2 of postmenopausal patients are not pharmacologically treated for OP post diagnosis. Reasons for non-treatment among recently diagnosed OP patients are not well understood. Objectives: To understand the physician perspective for not providing pharmacological treatment to women recently diagnosed with OP in France. Methods: An online survey was conducted among physicians from Nov 21-Dec 22 2014. The survey evaluated physician perceptions toward the screening, diagnosis, and management of OP. Physicians also completed a patient chart review by randomly selecting at least 3 patient charts that met all of the following criteria: postmenopausal female; diagnosed with OP within the past 3 to 12 months; not yet prescribed prescription OP medications. Patient clinical characteristics, OP risk factors, and reasons for non-treatment were collected for each chart reviewed. Results: 144 physicians completed the survey (67 primary care physicians, 30 geriatricians, and 47 rheumatologists) and data from 544 untreated postmenopausal OP patients charts were obtained. On average, 30% of postmenopausal women who had been newly diagnosed with OP were not pharmacologically treated for OP. Based on data from the patient charts, the majority of untreated patients (63%) were over age 60; 71% were diagnosed via bone mineral density scans (average t-score: -2.7) and had been diagnosed for an average of 6.2 months (median: 6 months). The primary reason for non-treatment was patient driven [patient pushed back on the recommended prescription (56%, n=306)], rather than physician driven, [physician decided not to prescribe (44%, n=238)]. The most frequently mentioned reasons for patient pushback included concerns of medication side-effects (56%), lack of understanding OP risks (30%), poly-pharmacy (25%), questioning the potential benefit of taking medication (25%), consideration of non-prescription options before prescription medications (24%), and difficulty in adhering to medication routine (23%). Physicians decided not to prescribe due to patients' low calcium and/or vitamin D levels (25%), polypharmacy (22%), borderline patient cases (t-score of -2.5 or -3.0 with no risk factors; 21%), and pre-existing gastrointestinal (GI) problems (20%) [Figure ]. For 49% of untreated patients, physicians intended to address patient concerns regarding the OP medications during the next patient visit. Conclusions: The absence of treatment for OP is driven by several patient and physician-driven factors. For patients, resistance included concerns about medication related side effects (56%) and patients' lack of understanding of the risks of OP (30%). Clinical issues such as low calcium and/or Vitamin D levels (25%), poly-pharmacy (22%), borderline cases of OP (21%), and pre-existing GI problems (20%) were the major physician-led reasons for non-treatment. References: Cortet B. Use of strontium as a treatment method for osteoporosis. Curr Osteoporos Rep. 2011;9(1):25-30. Modi A, Fan T, Sajjan S, Rajagopalan S, Sen S. Characteristics and treatment initiation among women diagnosed with osteoporosis in France. Osteoporosis International. 2012;23:S194. Acknowledgements: This research was funded by Merck, Inc USA. Disclosure of Interest: K. Olsson Employee of: Evidera, R. Sadasivan Employee of: Evidera, J. Weaver Employee of: Merck, S. Sen Employee of: Merck, A. Modi Employee of: Merck